HAZARDS IDENTIFICATION AND RISK ASSESSMENT OF PHYSICAL AND MECHANICAL FACTORS OF FORKLIFT OPERATIONAL IN PT SINAR INDOGREEN KENCANA AAC PRODUCTION AREA’S - Elya Maula Imro’atul Khasanah; Erwin Dyah Nawawinetu (Journal of Vocational Health Studies)
Background: Forklift is one of the most used craning plane in the manufacture and logistics industry. The operational of forklift can cause fatality work accident. PT SIGK uses forklift in the daily production activities, so it is necessary to identify hazard and risk assessment. Purpose: This study was to identify and assess the risk of physical and mechanical hazard at every stage of forklift operation. Methods: The type of this research was descriptive observational research, the object of the study were potential hazard and risk of all forklift operation stages in the AAC production area, consisted of 4 stages which were initial inspections stage, operational preparation stage, operational stage and post operations stage. Results: The result showed that there were 25 hazards, which were 4 hazards at the initial inspections stage, 2 hazards at the operational preparations stage, 14 hazards at the operational stage and 5 hazards at the post operations stage. Initial risk assessment obtained 2 hazards with high risk level, 22 hazards with medium risk level and 1 hazard with low risk level. The most prevalent hazard controls performed by PT SIGK were administrative (SOP, for klift training, safety sign) and PPE (helmet, gloves, mask), the controls got the value of effectiveness between 50% to 75%. Residual risk assessment, obtained 5 hazards with medium risk level and 20 hazards with low risk level. Conclusion: Additional control should be done by the company to reduce the residual risk level of medium category to be low, if the control recommendation is implemented well then the overall level of residual risk with low category will be obtained.